Desain Kegiatan Praktik dan Pengembangan Video Tutorial Pengujian Anti Bakteri Menggunakan Prosedur “ANKER” - Renardi Erwinsyah Putra; Cahyo Puji Asmoro; Siti Nur Hofifah (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
The design of practical activities for testing anti-bacterial sensitivity in microbiology practice, often only reach the verification stage using model recipe guidance. It is suspected that the recipe model laboratory activity design has not been able to construct student knowledge. The aim of this research is to develop a video tutorial for anti-bacterial sensitivity testing using VEE diagrams based on the ANKER procedure. The research method chosen was descriptive research through object scoring and even VEE diagrams, The research object was the design of anti-bacterial testing practice activities. Data sources were obtained from documentation studies, observations and interview surveys. Supervision video tutorials resulting from the design reconstruction of practical activities were tested on respondents and an assessment was carried out using a questionnaire survey to strengthen the research results. Scoring of the design of anti-bacterial sensitivity testing practice activities obtained 12 out of 18 points in the good category. Reconstruction of the practical activity design was carried out because the choice of tools and materials had not been identified. Next, video supervision of antibacterial testing was carried out as a result of the reconstruction of the design of practical activities. The results of the questionnaire showed that 72% of respondents thought that the video was suitable for use without improvement, and the remaining 28% thought that the video tutorial was suitable for use but needed improvement.